The Effective Of Solution Focused Brief Group Therapy (SFBGT) On Depression And Resilience Among Indonesian Women Migrant Workers In Malaysia - Purba, Ellys Juwita (2018)
Numerous studies have shown that there are high levels of morbidity due to mental turmoil among immigrants, principally depression and anxiety. Some of these studies disclose that migrant contact mentally depressed because they are strained with jobs that fall below their educational status. Women engage in recreation and rising role in international labour migration and presently constitute 49.6 percent of all labour migrants worldwide. At this time, Malaysia has 2.9 million acknowledged and about 3 million unacknowledged workers with the majority of them from Indonesia with a record of 50.9%.